Early Judaism and the Beginnings of Christianity : Common Roots and the Parting of the Ways - Tiwald, Markus (Kohlhammer Verlag, 2025)
Jesus and his first followers were Jews who never intended to form a new religion apart from Judaism. The so called "parting of the ways" between Jews and Christians was a complex process that stretched over five hundred years, occurring in different places at disparate velocities and under a variety of circumstances. Highlighting the pluriformity of early Judaism (300 BCE - 200 CE) in its political, sociological, economic, and religious implications, this book shows that what we today call the "beginnings of Christianity" was in fact an integral part of multifaceted Judaism.